2015
DOI: 10.1111/ajd.12294
|View full text |Cite
|
Sign up to set email alerts
|

Biological therapies for psoriasis: Adherence and outcome analysis from a clinical perspective

Abstract: We evaluated and compared patients' long-term adherence to biological therapies in a real-life clinical setting. Secondary aims included weight changes on biological therapy and reporting adverse effects. This prospective case-note review included 58 patients, undergoing 84 treatment series including etanercept (21), adalimumab (24), infliximab (14) and ustekinumab (25). Patients' adherence was greatest with ustekinumab (being 6.7-fold less likely to withdraw from treatment than etanercept, P = 0.014), while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 12 publications
6
32
0
3
Order By: Relevance
“…Biologic agents have shown relatively good adherence rates, ranging from 58% to 100%, which is higher than the adherence rates reported for oral therapy . In two trials including only psoriasis patients, ustekinumab showed the best overall adherence rate among systemic therapies studied (acitretin, methotrexate, adalimumab, etanercept, infliximab) . Comparing the adherence rates of different anti‐tumour necrosis factor alpha agents, infliximab had better results than adalimumab and etanercept .…”
Section: Factors Influencing Treatment Adherencementioning
confidence: 88%
“…Biologic agents have shown relatively good adherence rates, ranging from 58% to 100%, which is higher than the adherence rates reported for oral therapy . In two trials including only psoriasis patients, ustekinumab showed the best overall adherence rate among systemic therapies studied (acitretin, methotrexate, adalimumab, etanercept, infliximab) . Comparing the adherence rates of different anti‐tumour necrosis factor alpha agents, infliximab had better results than adalimumab and etanercept .…”
Section: Factors Influencing Treatment Adherencementioning
confidence: 88%
“…Nevertheless, until recently, there was only a lack of data obtained on large patient population treated for long time with TNF-alpha inhibitors and IL-12/23 inhibitor in the real-life settings (11,15). Table 3 summarizes all the studies published so far, where data were collected from large patient population of two or more centers, the follow-up period was at least one year, and the authors compared at least three or more biological therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Biologics that have prolonged drug survival rates are associated with superior efficacy and safety profiles . In addition, prolonged treatment adherence is noted as a surrogate measure for treatment success . The predictive factors for survival of biologics remain unclear, as no pooled analysis of these data has, to our knowledge, been performed yet.…”
mentioning
confidence: 99%